Alterações bioquímicas em espécies do gênero Alternanthera quando expostas à radiação UV-B e UV-C - Klein, Fátima Rosane Schuquel (2014)
The knowledge about ultraviolet (UV) effects in medicinal plants is still limited when compared with what is already known about other environmental factors. To investigate this issue we carried out two experiments: the first aimed to study the production of betalains, total flavonoid, and antioxidant activity in plants of Alternanthera sessilis, Alternanthera brasiliana, Alternanthera tenella, and Alternanthera philoxeroides, which were exposed to UV-B radiation (280-315 nm) for different periods; the second performed the same analyses, adding the investigation of the antioxidant enzymes in A. sessilis, A. brasiliana, and A. philoxeroides, submitted to UV-C (100-280 nm) for different periods of exposure. In the first experiment, the plants grown for 50 days in greenhouse were exposed to different UV-B irradiation periods (0, 2, 4, 6, and 8 hours). The collections were conducted in two periods, immediately after each exposure time (0h) and after 24 hours, to view a possible recovery. During the period inside the greenhouse, the plants remained under natural light. The experimental design was completely randomized, in 4 x 5 x 2 factorial scheme with five replicates by treatment, each one represented by a plant. Among the species studied, A. sessilis showed higher levels of total betacyanins, betaxanthin, flavonoids, and greater antioxidant capacity compared to other species throughout the period of exposure to radiation. We observed that in the species A. sessilis and A. brasiliana the recovery time favored an increase in the production of these compounds. The species A. tenella and A. philoxeroides showed no increase in the production of their metabolites, after UV-B radiation exposure. A randomized experiment in factorial design 3 x 5 was conducted to analyze the effects of UV-C radiation with three species A. sessilis, A. brasiliana, and A. philoxeroides for times intervals of 0, 5, 10, 15, and 20 min, with five replicates for treatment. A. sessilis showed a higher increase in metabolites under UV-C radiation between 10 and 12 minutes of exposure; in A. brasiliana it was observed after 16 minutes of exposure. The species A. philoxeroides showed no increase in its content after irradiation, remaining equal to control. For the activity of the enzyme superoxide dismutase (SOD), the species showed no significantly differences, but for catalase (CAT) and ascorbate peroxidase (APX) showed greater activity. An increase in malondialdehyde (MDA) content under UV-C radiation was viewed in A. philoxeroides and A. sessilis. In this experiment it was observed that both radiations caused changes in the content of total betacyanins, betaxanthin, and flavonoids in the species A. sessilis and A. brasiliana, and UV-C radiation changed enzymatic activity only in the species A. philoxeroides. These changes depend on the time exposure to radiation and the defense mechanisms triggered.